(untitled) (Edad Media. Revista de Historia, 2019)
Throughout the 1500s, there was a steady expansion of agrarian farmland within the Valencia de Alcántara area. Communalised fields became widespread across Extremadura and possibly other areas in the Crown of Castile, in association with the development of an agro-ecosystem clearly intended for integrated crop-livestock farming: the land was not divided and organised into compact spaces destined exclusively for cereal crop production, for within its limits it encompassed tapados (enclosed plots), facilities for animal husbandry, as well as uncultivated land. Farmland in Valencia de Alcántara became, thus, the product of both physical factors and collective management, resulting in a form of land distribution that was flexible enough to respond to short-term stimuli and still guarantee its own continuity.